Differential Neural Network Identification for Homogeneous Dynamical Systems. Issue 16 (2019) - Ballesteros, Mariana; Polyakov, Andrey; Efimov, Denis; Chairez, Isaac; Poznyak, Alexander
Abstract: In this paper, a non parametric identifier for homogeneous nonlinear systems affine in the input is proposed. The identification algorithm is based on the neural networks using sigmoidal activation functions. The learning algorithm is derived by means of Lyapunov function method and homogeneity theory. A numerical example demonstrates the performance of the proposed identifier.